The struggle for Aboriginal rights : a documentary history - Attwood, Bain.; Markus, Andrew (St Leonards, N.S.W. : Allen & Unwin, 1999)
This text tells the history of the political struggle for Aboriginal rights throughout Australia through a selection of historical documents created by Aboriginal campaigners. Using the words of native activists over 150 years, the book charts the relationship between involvement and identity.
Includes index.
Bibliography: p. [357]-362.
Keywords: Aboriginal Australians -- Politics and government; Aboriginal Australians -- History; Aboriginal Australians -- Legal status, laws, etc; Aboriginal Australians -- History -- Sources; Politics and Government - Political action - Anti racism; Politics and Government - Political action - Petitions; History; Attitudes - Indigenous perspectives; Politics and Government - Political action - Land rights; Politics and Government - Political action - Civil rights; Race relations; Australia